Determinants of Call Centre Employee’s Turnover in Pakistan - An Exploratory Study - Fatima, Syeda Zain; Naseem, Hafiza Iram (Archives of Business Research, 2021)
The purpose of this study was to find the determinants of call centre employee’s turn over in Pakistan. This study would answer Why employees quit call centres job in Pakistan and does not last for long. Little is known about the employs experience and real issue, that why did they quit. Eight employees were interviewed who have worked in the call centres. The interviews were qualitative and were analysed by drawing on the phenomenological method. The employees revealed that there are limited career opportunities in the call centres. Most participants stated that time schedule, stressed working environment and excessive work load were that major factor which urged them to quit the job too early. Participants stated the time schedule as a major factor which negatively impacted on their social and personal lives. In conclusion, this research provides the basis for human resource management to work on the real factor which spark the employee turnover in call centres of Pakistan.